Sex differences in total frontal plane knee movement and velocity during a functional single-leg landing. (March 2017) - Jenkins, Walter L.; Williams, D.S.Blaise; Williams, Kelsey; Hefner, Josh; Welch, Hannah
Abstract: Objectives: Females land with more knee valgus than males. While most studies have evaluated lower extremity mechanics during double leg landing, most sports require single-leg landing from a double or single leg takeoff. Further, knee movement occurs toward both varus and valgus during functional landing. The purpose of this study was to determine if differences exist between females and males in total frontal plane movement and velocity of the knee during single-leg landing. Design: Experimental cohort. Setting: Motion analysis laboratory. Participants: Forty healthy, physically-active females (n = 20) and males (n = 20). Main outcome measures: Three-dimensional motion analysis was completed on the lower extremities during double-leg jumping followed by a single-leg landing. Student's t-tests (p ≤ 0.05) were used to determine if differences exist in frontal plane knee angles (valgus and varus excursion) and angular velocities between females and males. Results: Females demonstrated greater knee valgus and varus excursion, and valgus and varus velocities compared to males (p < 0.05). Conclusions: These findings suggest that total movement in the frontal plane at the knee may be an important factor in injury mechanics in females. Further, single-leg landing from a functional jump should be considered when comparing landing biomechanics between females and males. Highlights: Females demonstrate greater frontal plane knee movement compared to males. Varus and valgus motions during landing occur at a higher rate in females. Single-leg landing results in different mechanics compared to double-leg landing. Knee varus motion is not necessarily a positive compensation during landing. A threshold of movement in both varus and valgus that should be considered.